Territorial redefinition and the governance of mountain regions - Gilles Rudaz (Revue de Géographie Alpine)
The claim that mountain regions have a specific character is today at the heart of a number of collective actions. The process of distinguishing territories redefines the status of mountain areas, reformulates the issues and content of projects that concern them, and redefines the actors involved and the relations they foster. All these changes have implications for the governance of territories. This article, which discusses actors’ positions and the legitimization of mountain entities, is not based on a particular case study but refers to a variety of examples taken from different mountain areas of the world to illustrate the processes underway.